2016
DOI: 10.5574/ksoe.2016.30.6.431
|View full text |Cite
|
Sign up to set email alerts
|

Study on Performance of Asymmetric Pre-Swirl Stator according to Variations in Dimensions and Blade Tip Shape

Abstract: 서 론최근 , 1993;Lee et al., 1992;Lee et al., 1994

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Regarding stator design, the pitch angle is the most important factor. In a previous study [24], the potential-based pitch design showed a good correlation with the experimental results. In the case of duct design, the duct angle is determined by aligning the flow direction through CFD computation [26], and NSMB Nozzle 19A was adopted for the present foil shape.…”
Section: Design Of Ring Statorsupporting
confidence: 55%
See 1 more Smart Citation
“…Regarding stator design, the pitch angle is the most important factor. In a previous study [24], the potential-based pitch design showed a good correlation with the experimental results. In the case of duct design, the duct angle is determined by aligning the flow direction through CFD computation [26], and NSMB Nozzle 19A was adopted for the present foil shape.…”
Section: Design Of Ring Statorsupporting
confidence: 55%
“…Adjusting the variable pre-swirl stator changes the circulation force Г for each radius. Since Г expresses the load applied to the blade, the performance can be compared through [24]. The PASTA program expresses Г as an equivalent angle of attack, α E , to enable intuitive analysis.…”
Section: Potential Analysismentioning
confidence: 99%
“…The interaction between propeller and stator is considered by iterative scheme and in that case the treatment of stator's wake has to be carefully done. Lee et al [15] and Shin et al [16] determined the pitch angle of an asymmetric pre-swirl stator using the PASTA program and found that the efficiency increased by 4-5%. However, the optimal pitch angle corresponding to maximum efficiency needs to be verified.…”
Section: Fig 3 Profile Of An Asymmetric Pre-swirl Statormentioning
confidence: 99%
“…where G is non-dimensional circulation as given by G = In the present study, the asymmetric pre-swirl stator proposed by Shin et al [16] was used, as shown in Tables 1 and 2. The equivalent incident angle is verified, as shown in Fig.…”
Section: = ρVmentioning
confidence: 99%
See 1 more Smart Citation